SPIRITUALITY IN THE AGE OF ARTIFICIAL INTELLIGENCE: A PERENNIAL PHILOSOPHICAL CRITIQUE OF THE FUTURE OF HUMANITY - Syaifuddin Zuhri; Nurul Huda (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
The rapid advancement of Artificial Intellegent (AI) has fundamentally transformed various dimensions of contemporary human life, including economics, education, communication, and religious practices. While AI provides unprecedented oppurtunities for efficiency, innovation and knowledge production, it also raises profound philosophical and spiritual conserns regarding the nature of humanity, meaning, and transcendence. This article examines the implication of AI development through the lens of perennial philoshophy, particularly the ideas of Rene Guenon, Frithjof Schuoen, and Seyyed Hossein Nasr. Employing a qualitative library research method, this study analyzes classical perennial text alongside contemporary literature on AI, digital culture, and spirituality. The findings reveal that AI represent the culmination of modern rationality and contributes to the increasing desacralitzation of human consciousness. The emergence of algorithmic  society, digital spirituality, and transhumanist discourse reflects a broader crisis of meaning rooted in the separation of knowledge from trancendent reality. From a perennial perspective, the challenge posed by AI is not merely technological but fundamentally metaphysical and spiritual. The study argues that the future of humanity depends on the integration of technological innovation with spiritual wisdom. Perennial philosophy offers an alternative frame work reconstructing spirituality in the digital age by reaffirming the secred dimension of knowledge, strengthening contemplative practices, and promoting a value-based ethics of technology. Ultimately, AI should serve humanity's spiritual flourishing rather than become the dominant orientation of civilization.